2022
DOI: 10.32322/jhsm.1037607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hospital acquired infections in the tertiary intensive care unit: a three-year analysis

Abstract: Introduction: Hospital-acquired infections (HAI) occurring in intensive care units (ICUs) are an important risk factor for mortality and morbidity. In some patient groups followed in ICUs, the risk of developing nosocomial infections increases even more. Especially, patients with end-stage renal disease (ESRD) carry a serious risk for HAI when they are hospitalized in ICUs. Our aim is to determine the rate and incidence of hospital infection, the distribution of infections and the most common microorganisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…(7.3%), CNS (5.3%), and S. aureus (4.5%) [ 40 ]. In another study conducted in our country, it was reported that the most common HAIs in ICUs were BSI, VAP, CA-UTI, CLABSI, and A. baumannii , K. pneumoniae , Enterococcus spp., and P. aeruginosa were the most common causative pathogens in these infections [ 41 ]. Although the incidence varies by facility and ICU type, the most often found HAIs in our research are BSI, pneumonia, and UTI, and the most common HAI pathogens, particularly Acinetobacter and Klebsiella species, are gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…(7.3%), CNS (5.3%), and S. aureus (4.5%) [ 40 ]. In another study conducted in our country, it was reported that the most common HAIs in ICUs were BSI, VAP, CA-UTI, CLABSI, and A. baumannii , K. pneumoniae , Enterococcus spp., and P. aeruginosa were the most common causative pathogens in these infections [ 41 ]. Although the incidence varies by facility and ICU type, the most often found HAIs in our research are BSI, pneumonia, and UTI, and the most common HAI pathogens, particularly Acinetobacter and Klebsiella species, are gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%